The role of cyber security in the Iranian security strategy (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study addresses the issue of the change in the concept of security threats due to developments in the field of technology, as the issue of cyber security has become one of the major challenges faced by countries at the regional and global levels, especially with the increasing volume of cyber threats that affect the information security of countries.Today, cyber security is one of the most important concepts that countries seek to achieve, especially after technological progress and the extent of the impact of this progress on the national security of countries, which necessitated the development of defensive security strategies to repel cyber-attacks and work to develop the cyber capabilities of countries.This study will focus on the most important concepts in cyberspace and the main actors in the practice of cyber-attacks, in addition to identifying the Iranian security strategy in the cyber field.The study reached results and recommendations, the most important of which is that cyberspace has become a new arena for international conflict and the need to develop defensive strategies to repel and detect cyber attacks.